Adoption and impact of management standards - Position paper - Tenera, Alexandra B. (2021)
Standardization makes its contributions to many aspects of our lives, although often that contribution is unnoticed. For example, management standards, such as the ISO 9000 family, establish a common ground perspective that enlarges companies' markets and boosts its international reaching, technological development, and innovation while supporting continuous quality improvement in products and services both at a national and international level. Notwithstanding the recognized relevance of some management standards, especially the ones that have an associated certification system to support its knowledge (e.g., ISO 9000 family), little is known about the impact of the standards (e.g., ISO 21500 family) adoption in increasing organizations' performance regarding, for instance, quality, safety, efficiency, or interoperability. This hinders the standards' dissemination and potential use and unnecessarily delays its revision and further development. To help fill this gap, this position paper proposes a research project that includes the development of a model and an observatory focusing on the adoption of management standards. The expected contributions are: 1) at a theoretical level, a new conceptual model for the explanation and assessment of the adoption of management standards and related impacts; 2) at a practical level, a new information system (observatory) which is expected to be a tool for understanding the adoption of standards, as well as for monitoring and publicizing the results obtained from standardization practices.